Memperkuat moderasi beragama dalam keanggotaan gereja distrik. Kecamatan Tanah Putih. Rokan Hilir, Provinsi Riau - Alvi Elsa Damayanti; Dewangga arya mukti (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This article is about strengthening religious moderation in church communities in Tanah Putih District, Rokan Hilir Regional Government Area, Riau Province. Through a participatory approach, churches and church associations play an important role in planning and implementing aid programs that encourage the active participation of local communities. Space for inclusive dialogue. The results of the study show that the Tanah Putih area has succeeded in embracing religious diversity, creating a peaceful environment and becoming an inspiring example of religious moderation as a solid foundation in everyday religious life. Strategy for Strengthening Religious Moderation in Various Religious Communities in Indonesia.